Growth centres in spatial planning - Moseley, Malcolm J. (Urban and regional planning series, 1974)
Growth Centres in Spatial Planning examines the role of growth centers in spatial planning in terms of achieving the intended objectives. Intended objectives include improving a region's potential for adopting innovations, a saving in public investment on infrastructure, a more efficient pattern of service provision, a dissemination of growth impulses throughout the problem region, and the interception of would-be migrants from the region. More specifically, this book analyzes the extent to which growth-center policies are likely to attain these objectives and how such policies might be modifi.